Modeling Tumor Vasculature Molecular, Cellular, and Tissue Level Aspects and Implications - Jackson, Trachette L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
To profoundly understand biology and harness its intricacies for human benefit and the mitigation of human harm requires cross-disciplinary approaches that incorporate sophisticated computational and mathematical modeling techniques. These integrative strategies are essential to achieve rapid and significant progress in issues, in health and disease, which span molecular, cellular and tissue levels. The use of mathematical models to describe various aspects of tumor growth has a very long history, dating back over six decades.  Recently, however, experimental and computational advances have improved our understanding of how processes act at multiple scales to mediate the development of tumor vasculature and drive the advancement of cancer. This book will showcase the development and utilization of new computational and mathematical approaches to address multiscale challenges associated with tumor vascular development.
A stochastic model of the vascular endothelial growth factor (VEGF) receptor:  Implications for cancer therapy -- Simulating therapeutics using multiscale models of the VEGF receptor system in cancer -- Linking EC Stimulation to Tumor Growth and Vascular Density:  The VEGF-BCL2-CXCL8 pathway -- Investigating the Role of Cross-Talk Between Chemical and Stromal Factors in Endothelial Cell Phenotype Determination -- A Hybrid Discrete-Continuum Model of Tumor Induced Angiogenesis -- Cell-based Models of Angiogenesis -- A cell-based model of endothelial cell migration, proliferation, and maturation in corneal angiogenesis -- Blood flow and tumour-induced angiogenesis: Dynamically adapting vascular networks -- Modeling structural and functional adaptation of tumor vessel networks during anti-angiogenic therapy -- Effect of vascularization on glioma tumor growth -- Particle Simulations of Growth:  Application to Tumorigenesis -- Particle Simulations of Growth:  Application to Angiogenesis -- Blood vessel network remodeling during tumor growth -- Blood perfusion in 3D solid tumour with “normalized” microvasculature.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.